“Fizz Enjoyable Sdn Bhd ” Blueprint Report / Zulhafizah Afra Zulkefli - Zulkefli, Zulhafizah Afra (2020)
Fizz Enjoyable SDN BHD is a sole proprietorship business that supply a very easy, useful and affordable product. It produces a unique with higher technology which very useful in our daily life named Temperature Controlled Insulated Mug. It allows user to have their simple mug that can easy to bring it anywhere. The technology that was provided for this mug is the rotating system that allow user to setting up their temperature of water